Cergam Digital sebagai Alternatif Media Pendukung Pemerolehan Bahasa Reseptif Anak Usia Dini di Tk Bina Putra 1 Wonorejo Kabupaten Demak - Sri Supriyani; Amalia Fajriyyatin Najichah (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
Digitalization in education has many benefits, but it is also a problem for early childhood learning if not applied appropriately. Bina Putra 1 Wonorejo Kindergarten, Demak Regency has a learning innovation using digital media as an alternative medium to support early childhood receptive language acquisition. This is the basis of this study with the aim of knowing the implementation, supporting factors, and inhibiting factors in this learning. This research is a qualitative research with case study type. The subjects in this study were 25 students of Group B of Bina Putra 1 Wonorejo Kindergarten, Demak Regency. Research data were obtained through observation, interviews, and documentation. The data obtained were analyzed using qualitative descriptive analysis techniques. The results of this study indicate that, support from various parties and a well-organized learning design are the main factors for the smooth implementation of digital illustrated stories in receptive language learning at Bina Putra 1 Wonorejo Kindergarten, Demak Regency. This is also inseparable from the aspects of adequate facilities and infrastructure as well as competent educators. However, there are still obstacles in the learning process, namely technical obstacles related to the operation of tools and class conditioning at the beginning of learning. Nevertheless, the presence of school operators and accompanying teachers can support the learning process.